Integration of Digital Tools for Teaching and Learning of Islamic Studies Among Senior Secondary Schools in Ilorin Metropolis, Nigeria - Ayuba, Jibril Olaniyi; Abdulkadir, Sakinah; Mohammed, A. A. (STKIP Pesisir Selatan, 2025)
This study examined the integration of digital tools for teaching and learning of Islamic studies among senior secondary schools in Ilorin, Nigeria. The advent of digital technology has profoundly impacted the landscape of Islamic religious education. The Covid- 19 pandemic outbreak, accelerated the adoption of digital tools for teaching and learning management. For that reason, educational institutions transitioned to virtual learning environments, utilizing diverse digital platforms. A descriptive survey research design was employed for the study. Simple random sampling technique was used to select 503 respondents as sample size for this study. An adapted questionnaire was used to elicit information from the respondents for the study. The reliability of the instrument was carried out with reliability index of 0.77. These findings indicate that Islamic educational institutions values the incorporation of digital technology and websites for teaching and learning. This approach is seen as crucial for equipping students with a balance skill between the interest of the world and preparation for the hereafter. Also, the study identified several key skills necessary for effective knowledge acquisition such as, mobile app proficiency, internet literacy, smart phone familiarity, technical competence, communication, creativity, time management, flexibility skills, and pedagogical knowledge. The study concluded that the study’s findings highlight the importance of digital skills for both teachers and students, the positive impact of smart phone use on teaching and learning effectiveness, particularly on Islamic studies. Based on the findings, the study recommended that educational curricula should be updated to incorporate digital tools and resources, to ensure that students develop the necessary digital skills to thrive in the 21st century.